Comparative Transcriptomic Exploration Reveals Unique Molecular Adaptations of Neuropathogenic Trichobilharzia to Invade and Parasitize Its Avian Definitive Host. - Roman Leontovyč; Neil D Young; Pasi K Korhonen; Ross S Hall; Patrick Tan; Libor Mikeš; Martin Kašný; Petr Horák; Robin B Gasser (Public Library of Science (PLoS), 2016)
To date, most molecular investigations of schistosomatids have focused principally on blood flukes (schistosomes) of humans. Despite the clinical importance of cercarial dermatitis in humans caused by Trichobilharzia regenti and the serious neuropathologic disease that this parasite causes in its permissive avian hosts and accidental mammalian hosts, almost nothing is known about the molecular aspects of how this fluke invades its hosts, migrates in host tissues and how it interacts with its hosts' immune system. Here, we explored selected aspects using a transcriptomic-bioinformatic approach. To do this, we sequenced, assembled and annotated the transcriptome representing two consecutive life stages (cercariae and schistosomula) of T. regenti involved in the first phases of infection of the avian host. We identified key biological and metabolic pathways specific to each of these two developmental stages and also undertook comparative analyses using data available for taxonomically related blood flukes of the genus Schistosoma. Detailed comparative analyses revealed the unique involvement of carbohydrate metabolism, translation and amino acid metabolism, and calcium in T. regenti cercariae during their invasion and in growth and development, as well as the roles of cell adhesion molecules, microaerobic metabolism (citrate cycle and oxidative phosphorylation), peptidases (cathepsins) and other histolytic and lysozomal proteins in schistosomula during their particular migration in neural tissues of the avian host. In conclusion, the present transcriptomic exploration provides new and significant insights into the molecular biology of T. regenti, which should underpin future genomic and proteomic investigations of T. regenti and, importantly, provides a useful starting point for a range of comparative studies of schistosomatids and other trematodes.